Nt-proBNP DISCRIMINATORY ROLE BETWEEN SYMPTOMATIC AND ASYMPTOMATIC PATIENTS WITH SEVERE VALVULAR AORTIC STENOSIS - Emilija Antova; Lidija Petkovska; Marijan Bosevski; Jagoda Stojkovic; Nikola Hadzy-Petrushev; Andre Kamkin; Mitko Mladenov (Macedonian Academy of Sciences and Arts, 2018)
Background: The aim was to evaluate the Nt-proBNP discriminatory role between symptomatic and asymptomatic patients with severe aortic stenosis. Methods: 187 patients with severe valvular aortic stenosis, with normal EF > 50%, were included, 61 asymptomatic and 126 symptomatic. We used clinical, laboratory (Nt-proBNP) and echocardiographic parameters. Endpoints of monitoring (occurrence of event) were: the onset of symptoms in asymptomatic patients and death in both groups. Results: The symptomatic group with severe AS had a significantly higher means of Nt-proBNP, in comparison with the asymptomatic group. Nt-proBNP was a significant predictor for the risk of event occurrence (HR 1.4). In the group of severe AS without CAD (n = 101), the subgroup with Nt-proBNP above the cut-off value, took significantly higher percentage of patients with chest pain, fatigue and syncope. In the group with Nt-proBNP above the cut-off value, we had a significantly higher percentage of patients with severe AS without CAD, compared to those with CAD (n = 142). Nt-proBNP was negatively correlated with AVA and LVEF, whether the positive correlation was expressed for: LVEDd, LVEDs, IVSd, AV_Vmax, AV_MaxGrad, LVM and LA. Patients with Nt-proBNP above the cut-off, had a significantly lower event free survival, compared to patients with Nt-proBNP below the cut-off (n = 187; n = 101). Conclusion: The Nt-proBNP cut-off> 460 pg/ml was confirmed as a useful tool in the determination of event free survival in patients with severe AS. Nt-proBNP not only had relevance in the assessment of the severity of the disease, but also was a significant predictor for the risk of event occurrence.
Keywords: Aortic stenosis; N-terminal pro-B-type natriuretic peptide; Echocardiography; Aortic valve replacement